Antarktisches Meereis: Vergleichende Betrachtung von Modell- und Satellitendaten und daraus erkennbare Entwicklungen - Freund, Madeleine (2010)
During the research how far modeldata is showing the satelliteviews, there have been compared two modellexperiments, wich are intent to show the antarctic Sea-Ice coverage in a most realistic way, with satellitedata from NASA's SSMI/SMMR. In doing so could make conclutions about how good the modells are mirroring the reality. In detail the results between model- and satellitedata differ partly a lot. Belonging to this the temporal resolution of single months, where mainly the maximum and minimum Sea-Ice-Area vary, and the more exact examination of the five regions in which the antarctic has been split. There are mainly differences in the west Pacific Ocean and the Bellingshausen and Amundsen Seas. The regions, where deep water formation happens, Weddell- and Ross-Sea are reflect very good and for the whole Antarctic the modells yield adequate results, too. Contrary to the generall oppinion, the antarctic Sea-Ice Area is growing, the analysis of the Sea-Ice-development showed, that exclusively the last decades, since there are satellite measurements, the Sea-Ice-Area is growing but during the last 50 years there is a rather decrease. Further more it becomes clear, that the antarctic Sea-Ice is embossed of very strong varyations, which occur since mid end of the seventy years and partly a trend is little-noticed. This development could be very fundamental for the events in the oceans, because the interactions between Sea-Ice and ocean is playing an important role. In the polar regions the whole radiation budget of the planet is balanced about the release of the heat, which was taken up at the equator. A especial weighty aspect of the heatexchange between ocean and atmosphere is linked with the, in the Weddel- and Ross-Sea happened, deep water information, which is an important part of the meriodonal overtuning circulation (MOC). Moreover reside to discover, if there are atmospheric interactions par example with changes in temperature, too or with phenomena, which have global consequences like El Niño Southern ...